A study of clinical opinion and practice regarding circumcision. Issue 5 (1st November 2000) - Farshi, Z; Atkinson, K R; Squire, R
Abstract : AIM: To establish clinical opinion regarding appropriate indications for circumcision and to examine actual clinical practice. METHODS: A questionnaire was sent to all NHS hospital consultants in the Yorkshire region of the UK identified as having a role to play in the management of boys (under 16 years of age) requiring circumcision. Retrospective data on actual clinical practice during a three month study period were also collected via a simple proforma. RESULTS: Of 153 questionnaires sent, 64 were returned. Responses revealed varying opinions regarding appropriate indications for circumcision within each consultant group, and between paediatricians and surgeons. Surgeons were generally more inclined to recommend circumcision for each of the indications listed in the questionnaire. Analysis of clinical practice revealed that almost two thirds of procedures were carried out for phimosis, and nearly half of these children were under the age of 5 years. CONCLUSION: There are differences in the clinical opinions of surgeons and paediatricians on what constitutes an appropriate indication for circumcision. Paediatricians' opinions are generally more in line with current evidence than those of surgeons, possibly resulting in many unnecessary circumcisions.